2004
DOI: 10.1023/b:caco.0000036444.11655.be
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Exposure to Vinyl Chloride, Acrylonitrile and Styrene and Lung Cancer Risk (Europe)

Abstract: Several industry-based cohort studies have addressed the risk of lung cancer following exposure to vinyl chloride, acrylonitrile and styrene, with inconsistent results and usually without smoking adjustment. These exposures are addressed here in a large case-control study with full adjustment for smoking. Almost 6000 subjects were included in a case-control study conducted in seven European countries. For each job they held, local experts assessed the exposure to a number of occupational agents, including viny… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
58
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1
1

Relationship

6
3

Authors

Journals

citations
Cited by 75 publications
(58 citation statements)
references
References 31 publications
0
58
0
Order By: Relevance
“…In Moscow, the controls were frequency matched to the upper aerodigestive tract cancer cases by age, sex, and referral or residence area. In the other centers, controls overlapped with those for a parallel casecontrol study of lung cancer conducted according to an identical protocol (28)(29)(30). Because the lung cancer study was started earlier than the upper aerodigestive tract cancer study, we excluded controls if their interview date was >6 months earlier than the first interview date for the upper aerodigestive tract cancer cases.…”
Section: Methodsmentioning
confidence: 99%
“…In Moscow, the controls were frequency matched to the upper aerodigestive tract cancer cases by age, sex, and referral or residence area. In the other centers, controls overlapped with those for a parallel casecontrol study of lung cancer conducted according to an identical protocol (28)(29)(30). Because the lung cancer study was started earlier than the upper aerodigestive tract cancer study, we excluded controls if their interview date was >6 months earlier than the first interview date for the upper aerodigestive tract cancer cases.…”
Section: Methodsmentioning
confidence: 99%
“…The study includes 2,135 cases and 2,115 controls recruited in 15 centers of six countries in central and eastern Europe. Details on the study setup and on subject recruitment have been previously reported (6). Briefly, the study population consists of 370 individuals from Romania (161 cases-209 controls), 623 from Hungary (335 cases-288 controls), 1,370 from Poland (675 cases-695 controls), 727 from Russia (404 cases-323 controls), 490 from Slovakia (280 cases-390 controls), and 670 from Czech Republic (280 cases-390 controls).…”
Section: Methodsmentioning
confidence: 99%
“…The Central Europe study was conducted during 1998-2002 across six central European countries. Information on demographics, lifestyle factors, and occupational exposures were recorded upon personal interview using standardized questionnaires (17). The present analysis included 2,035 controls and 1,286 case subjects with an available plasma sample.…”
Section: Study Populationmentioning
confidence: 99%